2015
DOI: 10.7554/elife.07864
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular epistasis shaped the function and evolution of an ancient transcription factor and its DNA binding sites

Abstract: Complexes of specifically interacting molecules, such as transcription factor proteins (TFs) and the DNA response elements (REs) they recognize, control most biological processes, but little is known concerning the functional and evolutionary effects of epistatic interactions across molecular interfaces. We experimentally characterized all combinations of genotypes in the joint protein-DNA sequence space defined by an historical transition in TF-RE specificity that occurred some 500 million years ago in the DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 99 publications
4
107
0
Order By: Relevance
“…In this case, enhancement of nGRE-binding ability in the GR lineage and the loss of nGRE-binding ability in the MR and AncSR3 lineages were critical for development of divergent DNA specificity. Both computational and directed evolution studies have implicated epistasis as a primary factor in molecular evolution (34,35), and studies of historical protein divergence have established a major role for epistasis in specific cases (28,(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, enhancement of nGRE-binding ability in the GR lineage and the loss of nGRE-binding ability in the MR and AncSR3 lineages were critical for development of divergent DNA specificity. Both computational and directed evolution studies have implicated epistasis as a primary factor in molecular evolution (34,35), and studies of historical protein divergence have established a major role for epistasis in specific cases (28,(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of slow-evolving receptors have revealed instances in which, after a functional shift, subsequent “restrictive” substitutions can occur that prevent the direct reversal of receptor preference [9, 9092]. However, when we introduced the “reverse” TEE47∆EK substitution into the derived ancMDA5/LGP2a (ancMDA5/LGP2a TEE47∆EK ), we observed a complete reversion to the ancestral ancRLR function, in which blunt-ended and 5′ppp dsRNAs are bound with equal affinity ( p  > 0.13; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various mechanisms were proposed, including protein-ligand or protein-DNA binding [25,37,38••], protein conformation [33,39], and allostery [40]. However, protein stability appears to be the most prevalent mechanism of intramolecular epistasis [7,41••,42,43].…”
Section: From Protein Sequence Space To Protein Biophysicsmentioning
confidence: 99%
“…Some describe it as rampant [38] and pervasive [55], or even consider it a determining factor of the molecular evolution [22,56], whereas others view it as less important [57,58]. We return to the discussion of prevalence and mechanisms of epistasis later, after introducing the theoretical foundation of protein biophysics-population genetics mapping.…”
Section: From Protein Sequence Space To Protein Biophysicsmentioning
confidence: 99%